Pleomorphic adenoma of nasal septum: A case report - Paudyal, P; Pande, K; Pradhan, A; Shah, R; Upadhyaya, P; Thapa, S (Journal of Pathology of Nepal, 2017)
Pleomorphic adenomas are the most common benign tumor of the major salivary glands. Other rare sites for the occurrence of pleomorphic adenoma have been described in the larynx, pharynx, nasal cavity, lacrimal glands and trachea. We report here a case of intranasal pleomorphic adenoma arising from the nasal septum causing nasal obstruction which was clinically diagnosed as papilloma. Histopathology confirmed the diagnosis of pleomorphic adenoma.